Recent advances in engineering hydrogels for niche biomimicking and hematopoietic stem cell culturing - Huang, Xiaochan; Wang, Yuting; Wang, Tianci; Wen, Feiqiu; Liu, Sixi; Oudeng, Gerile (Frontiers in Bioengineering and Biotechnology, 2022)
Hematopoietic stem cells (HSCs) provide a life-long supply of haemopoietic cells and are indispensable for clinical transplantation in the treatment of malignant hematological diseases. Clinical applications require vast quantities of HSCs with maintained stemness characteristics. Meeting this demand poses often insurmountable challenges for traditional culture methods. Creating a supportive artificial microenvironment for the culture of HSCs, which allows the expansion of the cells while maintaining their stemness, is becoming a new solution for the provision of these rare multipotent HSCs. Hydrogels with good biocompatibility, excellent hydrophilicity, tunable biochemical and biophysical properties have been applied in mimicking the hematopoietic niche for the efficient expansion of HSCs. This review focuses on recent progress in the use of hydrogels in this specialized application. Advanced biomimetic strategies use for the creation of an artificial haemopoietic niche are discussed, advances in combined use of hydrogel matrices and microfluidics, including the emerging organ-on-a-chip technology, are summarized. We also provide a brief description of novel stimulus-responsive hydrogels that are used to establish an intelligent dynamic cell microenvironment. Finally, current challenges and future perspectives of engineering hydrogels for HSC biomedicine are explored.